2018
DOI: 10.3389/fneur.2017.00733
|View full text |Cite
|
Sign up to set email alerts
|

Functional Strength Training and Movement Performance Therapy for Upper Limb Recovery Early Poststroke—Efficacy, Neural Correlates, Predictive Markers, and Cost-Effectiveness: FAST-INdiCATE Trial

Abstract: BackgroundVariation in physiological deficits underlying upper limb paresis after stroke could influence how people recover and to which physical therapy they best respond.ObjectivesTo determine whether functional strength training (FST) improves upper limb recovery more than movement performance therapy (MPT). To identify: (a) neural correlates of response and (b) whether pre-intervention neural characteristics predict response.DesignExplanatory investigations within a randomised, controlled, observer-blind, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 113 publications
4
10
0
2
Order By: Relevance
“…The results of this study are consistent with those of other studies that investigated arm strength training. Hunter et al compared strength training with an active movement therapy and found similar improvements in function and activities of the upper extremity (27). Winstein et al found, despite a longer intervention duration (5 weeks) compared with our study (3 weeks), that strengthening interventions increased strength and improved activity in patients who have had acute stroke, but without group differences (28).…”
Section: Discussionsupporting
confidence: 54%
“…The results of this study are consistent with those of other studies that investigated arm strength training. Hunter et al compared strength training with an active movement therapy and found similar improvements in function and activities of the upper extremity (27). Winstein et al found, despite a longer intervention duration (5 weeks) compared with our study (3 weeks), that strengthening interventions increased strength and improved activity in patients who have had acute stroke, but without group differences (28).…”
Section: Discussionsupporting
confidence: 54%
“…Effects of the intervention analyzed in each study were measured through different outcome variables according to the type of analysis, type of intervention, pathology of the participants and the objectives of the study. Consequently, QALY was measured in all the studies conducting cost-utility analysis [ 13 , 14 , 17 , 18 , 20 , 21 , 22 , 27 , 28 , 31 , 32 , 34 , 39 , 40 , 41 , 42 , 43 , 46 , 49 , 50 , 51 , 54 ]. Other health outcomes were used including HRQL [ 14 , 27 , 28 , 31 ], daily life activities [ 22 , 52 ] or pain [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…The post-stroke rehabilitation protocols are extremely important to aid patients to improve their quality of life [23]. In fact, upper limb recovery becomes crucial to ensure independence in the performance of the activities of the daily living (ADL), such as drinking from a cup, bathing, or dressing [24]. Although the functional outcome of these therapies is heterogeneous in its nature, its success depends on various factors, such as appropriate timing and the choice of the most suitable rehabilitation program for each individual [25].…”
Section: Common Therapeutic Practicesmentioning
confidence: 99%